Structural design, modelling, material testing and construction of a new stone masonry arch bridge in Vila Fria, Portugal - Cristina Costa (2007)
This paper presents the main activities involved in the construction of a new stone masonry arch bridge, the Vila Fria Bridge located in the north of Portugal, as part of a wider multidisciplinary project. The paper briefly describes the main aspects related to the design, construction, the characterization of the adopted materials and the numerical simulations to support the undertaken choices from the construction to the beginning of the bridge service conditions.